Development of a list of affective competencies and behavioral indicators in Physical and Occupational Therapy - Bumanglag, Ma. Liezel V.
Background. Affective competencies, as demonstrated by behaviors acted upon by people, are essential components in providing optimal care and receiving trust from patients and clients of physical (PTs) and occupational therapists (OTs). If these are generated, PT and OT schools will not just be guided on how to inculcate them in their respective outcome-based education designs, but also in assessing their attitudes. The Commission on Higher Education developed program outcomes for PT and OT education that include a combination of the necessary knowledge, skills, values or attitudes that are to be expected of PT and OT graduates. This study developed a list of the necessary affective competencies and their behavioral indicators, and matched them with the program outcomes stipulated in the curriculum. Methodology. A sample of experts from different fields of practice in the PT and OT population groups completed three rounds of Delphi technique in creating a list of affective competencies and their corresponding behavioral indicators. Cronbach?s alpha and rankings were used to come up with the final list, after which the contents of the list were matched with each program outcome. Results and Discussion. The final affective competencies and their behavioral indicators for both professions were mostly reflective of the existing code of ethics of the professions, with some not stated explicitly but were reflected as such in the behavioral indicators of other competencies. The program outcomes were clustered into groups that reflect their demands from the students, and most of the affective competencies were matched repeatedly for the clusters, signifying importance of the affective competencies regardless if the cluster is cognitive or skills-based in nature. Some of these are compassion, ethical reasoning, excellence, integrity and professionalism for the PTs, and inquisitiveness and professionalism for the OTs. Conclusion and Recommendation. Development of affective competencies is necessary for the achievement of the POs stipulated for PT and OT graduates. Their behavioral indicators suggest that development of these competencies as early as during classroom learning may be necessary to the acquisition of these competencies and, in turn, achieving the POs.